2020
DOI: 10.1063/5.0027773
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular fragmentation and radiative cooling of isolated PAH ions: A quantitative study

Abstract: Time-resolved spontaneous and laser-induced unimolecular fragmentation of perylene cations (C 20 H 12 + ) has been measured on timescales up to 2 s in a cryogenic electrostatic ion beam storage ring. We elaborate a quantitative model, which includes fragmentation in competition with radiative cooling via both vibrational and electronic (recurrent fluorescence) de-excitation. Excellent agreement with experimental results is found when sequential fragmentation of daughter ions co-stored with the parent perylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…The decay curve analysis procedure could be applied to laser-induced decay measurements to track the evolution of the vibrational energy distribution on longer timescales 42,43 . It could also be applied in more complex situations where multiple species are present in the stored ion beam 12 or where competing channels yield decay curves that are challenging to model analytically 33,37 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The decay curve analysis procedure could be applied to laser-induced decay measurements to track the evolution of the vibrational energy distribution on longer timescales 42,43 . It could also be applied in more complex situations where multiple species are present in the stored ion beam 12 or where competing channels yield decay curves that are challenging to model analytically 33,37 .…”
Section: Discussionmentioning
confidence: 99%
“…The time evolution of the population distribution g(E, t) of intact OHPyr + and BrPyr + were simulated using the Master Equation approach 28 . Further details of the methodology are presented elsewhere 12 . The vibrational level density ρ(E) is computed using the the Beyer-Swinehart algorithm 29 .…”
Section: Master Equation Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11] for experiments on carbon anions and Refs. [10,[12][13][14][15] for PAH molecules and other carbon-containing ions. Studies of radiative cooling of cationic carbon clusters were reported in [16].…”
Section: Introductionmentioning
confidence: 99%